Kinesio Taping and Quadriceps Strengthening Exercise Reduce Osteoarthritis Pain: A Literature Review - Waskito, Aji Darwin Kurniawan; Rustanti, Marti; Sukadarwanto, Sukadarwanto (Jurnal Keterapian Fisik, 2023)
Background: Osteoarthritis is one of the most common degenerative diseases, not only in Indonesia but also throughout most of the world. This disease causes pain in sufferers. Kinesio taping has therapeutic effects for muscle function correction by increasing weak muscle strength and improving blood and lymphatic circulation. Quadriceps strengthening exercises are one form of strengthening exercise recommended to increase the strength of the quadriceps and lower extreme muscles. The purpose of this study was to determine the effect of kinesio taping and quadriceps strengthening exercises on reducing osteoarthritis pain based on the literature. Methods: This study was a literature review using PICOT analysis. Five databases were used, namely PubMed, Sage Journal, BMC, Science Direct, PEDro, and snowballing technique. After all articles were collected and checked for duplication and screening, 11 articles were accepted and analyzed from 223 articles. Results: In this literature study, the researchers searched for and selected articles from 223 titles to 11 titles that met the inclusion criteria. Nine of the eleven journals had an effect on knee OA pain.  Conclusion: Research on the effect of Kinesio Taping and quadriceps strengthening exercises on knee osteoarthritis pain was conducted using a literature study method, and eleven articles that passed the screening test showed that Kinesio Taping and quadriceps strengthening exercises have an effect on knee osteoarthritis pain.